The role of hospital management control in the evaluation of public policies : the case of the University Hospital Centres in Morocco - AMZIL, Elhachem; NAFZAOUI, Mohamed Achraf (Revue Internationale du Chercheur, 2024)
The recent health and economic crises have led to budgetary constraints in Moroccan University Hospital Centres (UHCs), resulting in increased demand for medical care. At the same time, financial autonomy has given UHCs new responsibilities and greater management autonomy. However, these establishments are frequently accused of "wasting" public funds, prompting questions from the supervisory authorities. Against this backdrop, the development and implementation of quality of care and socio-economic efficiency indicators, together with the introduction of measurement tools and the promotion of a results-based management culture, have simplified evaluation processes. The aim of this article is to demonstrate the essential role of management control, and in particular its various steering tools, in the evaluation of public policies within University Hospital Centres . This demonstration is based on an exhaustive literature review and an exploratory empirical approach comprising six semi-structured interviews.